Cluster polarization behavior of a MIMO system: Measurement, modeling and statistical validation of the correlation of its channel parameters - Konishi, Yohei (Animo Repository, 2010)
This paper presents clusterwise polarization characteristics based on an estimated MIMO channel of a small urban macrocell at 4.5 GHz. Polarization path gain, cross-polarization ratio, and co-polarization ratio characteristics as influenced by channel parameters such as delay, azimuth and elevation angle of arrival were investigated. Hypothesis testing was used as a verification of the results. This statistical verification clarifies the independence of polarization characteristics from an azimuth angle of arrival, whereas some correlation was found between the cross-polarization ratio and the elevation angle of arrival. The results also confirmed a log-normal cross-polarization ratio.